ARCHBISHOP JOSEPH PARECATTIL IN THE SECOND VATICAN COUNCIL: ENVISAGING A PASTORAL AGENDA FOR THE CHURCH IN INDIA - Pulikkan, Paul (Asian Horizons, 2012)
Archbishop Joseph Parecattil, the most important spokesperson of the Syro Malabar Church in the Council, was one who understood the call of aggiornamento given by Pope John XXIII. In the preparatory phases of the Council and in the actual sessions, Parecattil led the Indian bishops with his characteristic boldness, vision and with a conviction that all the innovations and renewal must be for the greater pastoral good of the people. In this article, we are looking at his yeomen contribution in the Council, analyzing his Vota to the Council, his interventions in the preparatory period and in the four sessions of the Council. He clearly shared the vision of Pope John XXIII and later that of Pope Paul VI that the Council is to lead the Church beyond the status quo, beyond a mentality that saw the Church as a fortress, looking at others as enemies and opponents. He sincerely believed that if the Catholic Church is to be really catholic, it must accept in its treasure house, the riches found in the non European cultures and traditions.